(untitled) - Necsulesscu, Dan (New Jersey, 2002)
For a first course in Mechatronics taught at senior undergraduate level in the departments of mechanical, electrical, computer and general engineering.This text provides a self-contained, modern treatment of the computer based mixed systems integration. The book covers fundamental topics starting with the physical properties, continuing with mathematical modeling and computer simulation and ending with applications illustrated by numerically and experimentally generated results. It explores all major topics in mechatronics and offers a detailed presentation of selected devices as well as numerous MATLAB, Simulink and LabVIEW applications.
Đồ án thiết kế hệ thống cơ điện tử
Keywords: Mechatronics